Innovative Aspects of Processing of Lithium Technogenic Raw Materials - ?. S. Yusupov; A. G. Vladimirov; S. A. Kondratiev; V. P. Isupov; N. Z. Lyakhov (International Mineral Processing Congress, 2018)
"Considering the shortage of lithium reserves, the desirability has been shown of studying the possibility of processing into spodumene concentrates the concentration tailings and low-grade ore reserves at Transbaikalian Mining and Processing Project (ZabGOK). The mineral and chemical composition and the particle size distribution of the mineral feed, separability and recoverability of spodumene have been studied, forming the basis for the development of a concentration process and flowsheet for the studied mineral resource. Prospects have been established for impact ore grinding in a disintegrator, the efficiency of mechanochemical processes has been shown in the separation of quartz and feldspar and the recovery of lithium from concentrates.INTRODUCTION Lithium is widely used in various industries - nuclear power engineering, defense technology, power generation, ceramics, special-purpose glass and other technologies. The increasing demand for lithium and its compounds (lithium carbonate and hydroxide) for use in the manufacture of high-tech products (lithium-based materials for chemical sources of electric power and electrochemical energy) explains the need for establishing a sustainable raw material base (Mohr et al. 2012; Moores, 2007). The main sources of lithium are spodumene pegmatites (Vladimirov et al. 2012; Garret, 2004), brines (salars), and hydromineral materials (Garret, 2004; Zeng and Liu, 2009; Kotsupalo and Ryabtsev, 2008). However, in view of the absence in Russia of extractable hydromineral resources of lithium, the practical significance of spodumene ores remains decisive. Russia controls some of the world’s largest reserves of rare-metal pegmatites holding over 8 million tons of Li2O: approximately 7 million tons on the Kola peninsula and 1 million tons in the Sayan mountains. The main lithium mineral in pegmatites is spodumene LiAlSi2O6 containing 8.1% Li2O. It can be efficiently recovered by gravitational concentration and flotation. However, most of the deposits are located in remote areas and none is currently developed. In this connection, special research is focused on technogenic raw materials, which are increasingly seen as a solution to the resource base problem (Chanturia, 2008, Kurkov and Kotova, 2007)."